Thirty-day outcomes in Indigenous Australians following coronary artery bypass grafting - O'Brien, J.; Saxena, A.; Reid, Christopher; Tran, L.; Baker, R.; Newcomb, A.; Smith, J.; Huq, M.; Duffy, S. (Blackwell Publishing, 2018)
Background: Indigenous Australians have higher rates of cardiovascular disease and comorbidities compared to their non-indigenous counterparts. Aims: We sought to evaluate whether indigenous status per se portends a worse prognosis following isolated coronary artery bypass grafting (CABG). Methods: The outcomes of 778 Indigenous Australians (55 ± 10 years; 32% female) enrolled in the Australian and New Zealand Society of Cardiac and Thoracic Surgeons registry were compared to 36 124 non-Indigenous Australians (66 ± 10 years; 21% female) following isolated CABG. In a secondary analysis, patients were propensity-matched by age, sex, renal function, diabetes and ejection fraction (778 individuals in each group). Results: Indigenous Australians were younger and more likely to be female and current smokers and to have diabetes, hypertension, renal impairment, heart failure and previous CABG (all P < 0.04). Indigenous patients had fewer bypasses with arterial conduits (including less internal mammary artery use) and a higher number of distal vein anastomoses (P < 0.001). Postoperative bleeding rates were higher in indigenous patients (P = 0.001). However, in-hospital and 30-day all-cause mortality and rates of 30-day readmission were similar between both groups, although cardiac mortality was higher in the indigenous cohort (1.5% vs 0.8%, P = 0.02). With propensity-matching, rates of postoperative complications were similar among the two groups, with the exception of bleeding, which remained higher in Indigenous Australians (P = 0.03). Conclusions: Despite procedural differences and higher rates of baseline comorbidities, Indigenous Australians do not have worse short-term outcomes following isolated CABG. Given the higher rates of baseline comorbidities and lower rates of arterial conduit use, it will be essential to determine long-term outcomes.